Coating film-forming composition and method for manufacturing semiconductor device
Patent Information
- Application Number
- CN201980024774.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-04-06
- Filing Date
- 2019-04-02
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2039-04-02
AI Technical Summary
Existing coating film forming compositions using formic acid as a pH adjuster are not suitable for industrial applications and are difficult to selectively form coating films on wiring layers containing copper and insulating layers such as silicon oxide.
A coating film is formed by coating and baking using a composition comprising a diallylamine polymer and a mixture of a specific organic solvent and water, and the coating film on the wiring layer is selectively removed using water.
It enables the selective formation of coating films on insulating layers, avoiding the use of restricted chemicals, and is simple, efficient, and suitable for industrial applications.
Smart Images

Figure CN111936588B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a coating film forming composition and a method for manufacturing a semiconductor device. Background Technology
[0002] In the field of miniaturized semiconductor devices, to prevent the diffusion of metallic components such as copper embedded in the interlayer insulating layer of a semiconductor as wiring material, the formation of a resin layer has been proposed (Patent Document 1). However, it is required that no resin layer be formed on the wiring to maintain the electrical connection on the wiring surface. Non-Patent Document 1 describes the use of a composition containing polyethyleneimine and pH adjusted with formic acid, which enables the selective formation of an organic film on SiO2.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: International Publication No. 2010 / 137711
[0006] Non-patent literature
[0007] Non-patent literature 1: J. Phys. Chem. C 2015, 119, 22882-22888 Summary of the Invention
[0008] The problem that the invention aims to solve
[0009] For the technology described in Non-Patent Document 1, formic acid must be added to the composition as a pH adjuster. Formic acid is designated as a hazardous substance under the Toxic and Hazardous Substances Control Law in Japan, and the use of materials containing formic acid is unsuitable for industrial application.
[0010] The present invention was made in view of the above-mentioned circumstances, and its object is to provide a coating film forming composition and a method for manufacturing a semiconductor device using the same, wherein the coating film forming composition does not use formic acid or other restricted chemical substances, and can selectively form a coating film on an insulating layer on a substrate having a wiring layer containing copper and an insulating layer represented by silicon oxide.
[0011] Methods for solving problems
[0012] In order to achieve the above objectives, the inventors conducted repeated and in-depth research and found that the above problems could be solved by using a composition containing a specified diallylamine polymer and a specified organic solvent and water as a mixed solvent, thus completing the present invention.
[0013] That is, the present invention provides the following coating film forming composition and method for manufacturing semiconductor devices.
[0014] 1. A coating film forming composition comprising
[0015] (a) A polymer containing structural units represented by formula (1a) or (1b) below, and
[0016] (b) A solvent comprising 1 to 49% by weight of at least one organic solvent selected from propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, methyl 2-hydroxyisobutyrate, ethyl 3-ethoxypropionate and ethyl lactate, and 51 to 99% by weight of water.
[0017] [Chemistry 1]
[0018]
[0019] (In the formula, X is acetic acid, propionic acid, aminosulfonic acid, or hydrogen halide, Y) - For hydrogen sulfate ions, methyl sulfate ions, ethyl sulfate ions, or halide ions, R 1 R is a hydrogen atom or a methyl group. 2 and R 3 Each can be either methyl or ethyl.
[0020] 2.1 The coating film forming composition, wherein the polymer further contains a structural unit represented by the following formula (2).
[0021] [Chemistry 2]
[0022]
[0023] 3. A coating film forming composition of 1 or 2, wherein (b) the solvent comprises 1 to 30% by mass of the organic solvent and 70 to 99% by mass of water.
[0024] 4. A method for manufacturing a semiconductor device, comprising: a step of coating a coating film forming composition of any one of 1 to 3 onto the surface of an insulating layer and a wiring layer comprising copper formed on a substrate, and baking to form a coating film; and a step of selectively removing the coating film on the wiring layer using water.
[0025] 5.4 A method for manufacturing a semiconductor device, wherein the insulating layer is mainly composed of SiO2.
[0026] 6.4 or 5. A method of manufacturing a semiconductor device, wherein the insulating layer is primarily composed of porous silicon dioxide and has silanol residues derived from the porous silicon dioxide on its surface.
[0027] The effects of the invention
[0028] The coating film forming composition of the present invention is industrially usable because it does not contain formic acid or other chemicals whose use is restricted. Furthermore, by using the coating film forming composition of the present invention, a coating film can be selectively and easily formed on an insulating layer. Detailed Implementation
[0029] [(a)Component]
[0030] The coating film forming composition of the present invention has component (a) as a diallylamine polymer containing structural units represented by the following formula (1a) or (1b).
[0031] [Chemistry 3]
[0032]
[0033] In formula (1a), X is acetic acid, propionic acid, aminosulfonic acid, or hydrogen halide. Examples of hydrogen halide include hydrogen chloride, hydrogen bromide, and hydrogen iodide. Acetic acid or aminosulfonic acid is preferred as X.
[0034] In equation (1b), Y - These can be hydrogen sulfate ions, methyl sulfate ions, ethyl sulfate ions, or halide ions. Examples of halide ions include chloride ions, bromide ions, and iodide ions. As for Y... - Ethyl sulfate ions are preferred.
[0035] In equation (1a), R 1 It can be a hydrogen atom or a methyl group. In formula (1b), R 2 and R 3 Each can be methyl or ethyl.
[0036] The polymer described above preferably also contains structural units represented by the following formula (2).
[0037] [Chemistry 4]
[0038]
[0039] In the case where the polymer is a copolymer containing structural units represented by formula (1a) or (1b) and structural units represented by formula (2), the copolymer may be an alternating copolymer in which structural units represented by formula (1a) or (1b) are alternately combined with structural units represented by formula (2), or a random copolymer in which these structural units are randomly combined, with alternating copolymers being particularly preferred.
[0040] The polymer described above may contain structural units other than those described above (hereinafter referred to as other structural units). Examples of other structural units include structural units derived from (meth)acrylamide, structural units derived from monoallylamines such as allylamine, N-methylallylamine, and N,N-dimethylallylamine, and structural units derived from acid addition salts of monoallylamines such as acetate, hydrochloride, hydrogen bromide, propionic acid, and aminosulfonic acid.
[0041] When the polymer in component (a) is the copolymer described above, the ratio of the structural unit represented by formula (1a) or (1b) to the structural unit represented by formula (2) is expressed as a molar ratio, preferably in the range of 99 / 1 to 50 / 50, more preferably in the range of 90 / 10 to 50 / 50, and even more preferably in the range of 50 / 50 or similar. Furthermore, when other structural units are included, their proportion in all structural units is typically 10 mol% or less, preferably 5 mol% or less.
[0042] (a) The weight-average molecular weight (Mw) of the polymer of component (a) is preferably 300 to 1,000,000, more preferably 500 to 500,000, even more preferably 800 to 100,000, and still more preferably 1,000 to 50,000. It should be noted that, in this invention, the Mw of the polymer of component (a) is a value converted from polyethylene glycol obtained by gel permeation chromatography (GPC).
[0043] The polymer used as component (a) can be synthesized using conventionally known methods or can be a commercially available product. Examples of the aforementioned commercially available products include those manufactured by Nitobomedecal Co., Ltd., such as PAA-D11-HCL, PAA-D41-HCL, PAA-D19-HCL, PAA-D19A, PAS-21CL, PAS-M-1L, PAS-M-1, PAS-22SA-40, PAS-M-1A, PAS-H-1L, PAS-H-5L, PAS-H-10L, PAS-24, PAS-92, PAS-92A, PAS-2401, PAS-2201CL, PAS-A-1, PAS-A-5, PAS-2141CL, PAS-J-81L, PAS-J-81, PAS-J-41, and PAS-880.
[0044] In the composition of the present invention, from the viewpoint of film-forming properties, the content of component (a) is preferably 0.1 to 20% by mass, more preferably 1 to 5% by mass.
[0045] [(b) Solvent]
[0046] (b) The solvent of the component comprises 1 to 49% by mass of an organic solvent selected from at least one of propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, methyl 2-hydroxyisobutyrate, ethyl 3-ethoxypropionate, and ethyl lactate, and 51 to 99% by mass of water. If the content of the above organic solvent is less than 1% by mass, the coatability may be reduced; if it exceeds 49% by mass, the solubility of the polymer of component (a) may be reduced.
[0047] As the organic solvent mentioned above, propylene glycol monomethyl ether or propylene glycol monomethyl ether acetate is preferred, and propylene glycol monomethyl ether is more preferred.
[0048] (b) In the solvent, the content of the above-mentioned organic solvent is preferably 1-30% by mass, more preferably 5-25% by mass, and even more preferably 10-20% by mass. The content of water is preferably 70-99% by mass, more preferably 75-95% by mass, and even more preferably 80-90% by mass.
[0049] [Other ingredients]
[0050] The compositions of the present invention may contain components other than those described above (hereinafter referred to as other components) without impairing the effects of the present invention. Various additives, such as surfactants, can be listed as other components. Surfactants are additives used to improve the coatability of the compositions of the present invention to a substrate. Known surfactants such as nonionic surfactants and fluorinated surfactants can be used as surfactants.
[0051] [Semiconductor device manufacturing method]
[0052] The method for manufacturing a semiconductor device according to the present invention includes: a step of coating the above-described coating film forming composition onto the surfaces of the insulating layer and the copper wiring layer on a substrate having an insulating layer and a copper wiring layer (hereinafter referred to as the copper wiring layer); baking to form a coating film; and a step of selectively removing the coating film on the copper wiring layer using water.
[0053] Examples of insulating layers include those containing SiO2, and those containing low-k materials such as porous silica, SiOF, SiOC, hydrogenated silsesquioxane, and methylated silsesquioxane. Among these, insulating layers with SiO2 as the main component are preferred, as are insulating layers with porous silica as the main component and having silanol residues from the porous silica on their surface. It should be noted that, in this invention, "main component" refers to the component with the highest content.
[0054] As a substrate on which the above-mentioned insulating layer and copper wiring layer are formed, examples include a substrate obtained by forming copper wirings from patterns formed in the insulating layer on a semiconductor substrate such as silicon using methods such as electroplating, and then planarizing it by chemical mechanical polishing (CMP). Alternatively, as a substrate on which the above-mentioned insulating layer and copper wiring layer are formed, examples include a substrate that, after CMP, further forms an insulating layer, multilayers, and forms trenches and through-holes.
[0055] The method for coating the above-mentioned coating film to form the composition can be a conventionally known method, such as spin coating, cast coating, doctor blade coating, dip coating, roller coating, bar coating, mold coating, inkjet coating, printing, etc.
[0056] After the above-described coating composition is applied to the surfaces of the insulating layer and the copper wiring layer on the substrate, baking is performed to form the coating film. The baking temperature is preferably 50–300°C, more preferably 70–250°C. The baking time is preferably 10 seconds to 10 minutes, more preferably 30 seconds to 2 minutes.
[0057] The thickness of the resulting coating film is preferably 0.1–200 nm, more preferably 1–100 nm.
[0058] After the coating film is formed, water is used to selectively remove the coating film from the copper wiring layer. Examples of methods for removing the coating film include applying water onto the coating film to dissolve and remove it from the copper wiring layer. Examples of water application methods include spin coating, cast coating, doctor blade coating, dip coating, roller coating, bar coating, mold coating, inkjet coating, and printing.
[0059] Using the method described above, an organic film can be selectively formed on the surface of the insulating layer. This organic film prevents the diffusion of metallic components from the wiring into the insulating layer and also functions as a protective film for the insulating layer.
[0060] Example
[0061] The following examples and embodiments illustrate the invention in more detail, but the invention is not limited to the following embodiments.
[0062] [Synthesis example 1]
[0063] 5.00 g of diglycidyl terephthalate (manufactured by Nagase ChemteX Corporation, Denacol EX711), 3.15 g of 5-hydroxyisophthalic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.20 g of benzyltriethylammonium chloride (manufactured by Tokyo Chemical Industry Co., Ltd.) were added to 35.60 g of propylene glycol monomethyl ether and dissolved. After purging the reaction vessel with nitrogen, the reaction was carried out at 135°C for 4 hours to obtain a polymer solution. The polymer has good solubility in propylene glycol monomethyl ether, and its solution does not produce turbidity even when cooled to room temperature. GPC analysis was performed (elution: tetrahydrofuran, calibration curve: standard polystyrene), and the results showed that the polymer in the obtained solution had a Mw of 15,673 and a dispersion of 3.39. The polymer obtained in this synthesis example has structural units represented by the following formula (3) and structural units represented by the following formula (4).
[0064] [Chemistry 5]
[0065]
[0066] [1] Preparation of coating film forming composition
[0067] [Example 1-1]
[0068] A coating film forming composition A was prepared by adding 11.2 g of ultrapure water and 3 g of propylene glycol monomethyl ether to 0.80 g of an aqueous solution containing 0.15 g of diallylamine acetate-sulfur dioxide copolymer (made by Nitob Boehmedica Co., Ltd., PAS-92A).
[0069] [Comparative Example 1-1]
[0070] In Synthesis Example 1, 1.3 g of a polymer solution containing 0.24 g of polymer solids was added to 1.3 g of polyethylene glycol monomethyl ether and 5.9 g of propylene glycol monomethyl ether acetate to prepare coating film forming composition B. The polymer contained in coating film forming composition B of this comparative example is not equivalent to a polymer containing structural units represented by formula (1a) or (1b) above.
[0071] [Comparative Examples 1-2]
[0072] A coating film forming composition C was prepared by adding 14.2 g of ultrapure water to 0.80 g of an aqueous solution containing 0.15 g of diallylamine acetate-sulfur dioxide copolymer (manufactured by Nitob Boehmédica Co., Ltd., PAS-92A). Regarding the solvent contained in the coating film forming composition C of this comparative example, the content of organic solvent was less than 1% by mass (0% by mass).
[0073] [Comparative Examples 1-3]
[0074] A coating film forming composition was prepared by adding 6.8 g of ultrapure water and 7.4 g of propylene glycol monomethyl ether to 0.80 g of an aqueous solution containing 0.15 g of diallylamine acetate-sulfur dioxide copolymer (manufactured by Nitob Boehmédica Co., Ltd., PAS-92A). However, polymer precipitation occurred in the coating film forming composition prepared in this comparative example. Regarding the solvent contained in the coating film forming composition of this comparative example, the content of organic solvent exceeded 49% by mass.
[0075] [2] Evaluation of coating film formation
[0076] For a substrate with silicon oxide deposited to a thickness of 300 nm (hereinafter referred to as SiO2 substrate), an O2 ashing process was performed for 10 minutes using an etcher manufactured by Samco Inc. The resulting SiO2 substrate was then cut into 3 cm square pieces for evaluating the coatability of the insulating layer. Additionally, the water contact angle of the aforementioned SiO2 substrate was measured using a contact angle meter DM-701 (manufactured by Kyowa Interface Science Co., Ltd.) as the water contact angle before film formation.
[0077] A copper substrate with a thickness of 100 nm (hereinafter referred to as the Cu substrate) was immersed in a 0.5 mol / L sulfuric acid solution for 5 minutes, then rinsed with ultrapure water and dried. The resulting Cu substrate was then cut into 3 cm square pieces for evaluating the coatability of the wiring layer. Additionally, the water contact angle of the Cu substrate was measured using a DM-701 contact angle meter (manufactured by Kyowa Interface Science Co., Ltd.) as the water contact angle before film formation.
[0078] [Example 2-1]
[0079] The coating composition A was applied to the aforementioned SiO2 and Cu substrates, each cut to 3 cm square, using a spin coater (manufactured by Brewer Technologies, Inc.). The coated films were then baked at 100°C for 60 seconds. Next, ultrapure water was applied to the coated films using a spin coater (manufactured by Brewer Technologies, Inc.) and held for 60 seconds. After removing the coating films from both the SiO2 and Cu substrates, the contact angle of the water was measured using a contact angle meter DM-701 (manufactured by Kyowa Interface Science Co., Ltd.). The results are shown in Table 1.
[0080] [Comparative Example 2-1]
[0081] The coating composition B was applied to the SiO2 and Cu substrates cut to 3 cm squares using a spin coater (manufactured by Brewer Technologies, Inc.), and baked at 100°C for 60 seconds to form a coating film. Then, a propylene glycol monomethyl ether / propylene glycol monomethyl ether acetate mixture of 7 / 3 (mass ratio) was applied to the coating film using a spin coater (manufactured by Brewer Technologies, Inc.), held for 60 seconds, and the coating film on the SiO2 and Cu substrates was removed. The contact angle of water was measured using a contact angle meter DM-701 (manufactured by Kyowa Interface Science Co., Ltd.). The results are shown in Table 1.
[0082] [Table 1]
[0083] Before membrane formation Example 2-1 Comparative Example 2-1 <![CDATA[SiO₂ substrate]]> 36° 42° 35° Cu substrate 101° 100° 55°
[0084] [Example 2-2]
[0085] Except that the baking temperature was set to 200°C, the water contact angle was measured using the same method as in Example 2-1. The results are shown in Table 2.
[0086] [Comparative Example 2-2]
[0087] Except that the baking temperature was set to 200°C, the water contact angle was measured using the same method as in Comparative Example 2-1. The results are shown in Table 2.
[0088] [Table 2]
[0089] Before membrane formation Example 2-2 Comparative Example 2-2 <![CDATA[SiO₂ substrate]]> 37° 69° 62° Cu substrate 100° 100° 49°
[0090] [Comparative Examples 2-3]
[0091] The above method was used to coat the coating film forming composition C on the SiO2 substrate and the Cu substrate, but uniform coating was not achieved on all substrates.
[0092] As can be seen from Examples 2-1 and 2-2, when a coating film is formed on a SiO2 substrate using the coating film forming composition A of the present invention, the contact angle changes before and after the coating film is formed, indicating that the coating film was not removed by water and remains on the SiO2 substrate. On the other hand, when a coating film is formed on a Cu substrate, the contact angle hardly changes before and after the coating film is formed, indicating that the coating film was removed by water.
[0093] Comparative Examples 2-1 and 2-2 show that when a coating film is formed on a Cu substrate using coating film forming composition B, the contact angle changes before and after its formation. This indicates that the coating film obtained by coating film forming composition B was not removed using a propylene glycol monomethyl ether / propylene glycol monomethyl ether acetate ratio of 7 / 3 (mass ratio), and remains on the Cu substrate. In other words, it indicates that the coating film obtained by coating film forming composition B was not removed from the Cu substrate using a propylene glycol monomethyl ether / propylene glycol monomethyl ether acetate ratio of 7 / 3 (mass ratio).
[0094] The results above demonstrate that by using the composition of the present invention, a coating film can be selectively formed on the insulating layer.
Claims
1. Use of a coating film forming composition for selectively forming a coating film on an insulating layer having a copper wiring layer and an insulating layer, the coating film forming composition comprising (a) A polymer containing structural units represented by formula (1a) or (1b) below, and (b) A solvent comprising 20-49% by weight of at least one organic solvent selected from propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, methyl 2-hydroxyisobutyrate, ethyl 3-ethoxypropionate, and ethyl lactate, and 51-80% by weight of water. In the formula, X is propionic acid, aminosulfonic acid, or hydrogen halide, and Y... - It is a hydrogen sulfate ion, methyl sulfate ion, ethyl sulfate ion, or halide ion, R 1 R is a hydrogen atom or a methyl group. 2 and R 3 Each can be methyl or ethyl independently.
2. The use according to claim 1, wherein, The polymer also contains structural units represented by the following formula (2), 。 3. The use according to claim 1 or 2, wherein, (b) The solvent comprises 20 to 30% by mass of the organic solvent and 70 to 80% by mass of water.
4. A method for manufacturing a semiconductor device, comprising: a step of coating a coating film forming composition onto the surfaces of an insulating layer and a copper-containing wiring layer on a substrate; baking to form a coating film; and a step of selectively removing the coating film from the wiring layer using water. The coating film forming composition is a coating film forming composition for selectively forming a coating film on an insulating layer on a substrate having a wiring layer containing copper and an insulating layer, comprising... (a) A polymer containing structural units represented by formula (1a) or (1b) below, and (b) A solvent comprising 1 to 49% by weight of at least one organic solvent selected from propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, methyl 2-hydroxyisobutyrate, ethyl 3-ethoxypropionate, and ethyl lactate, and 51 to 99% by weight of water. In the formula, X is acetic acid, propionic acid, aminosulfonic acid, or hydrogen halide, and Y is... - It is a hydrogen sulfate ion, methyl sulfate ion, ethyl sulfate ion, or halide ion, R 1 R is a hydrogen atom or a methyl group. 2 and R 3 Each can be methyl or ethyl independently.
5. The method for manufacturing a semiconductor device according to claim 4, wherein, The insulating layer is mainly composed of SiO2.
6. The method of manufacturing a semiconductor device according to claim 4 or 5, wherein, The insulating layer is mainly composed of porous silica, and its surface has silanol residues derived from the porous silica.
Citation Information
Patent Citations
Composition for sealing semiconductor, semiconductor device, and process for manufacturing semiconductor device
WO2010137711A1
Method for manufacturing complex, and composition
CN105051872A
Copolymer dispersion for water-borne coating agent and water-borne coating agent
JP2001123106A
Application composition for semiconductor element protecting film
TW200946614A
Treatment liquid, ink set, and inkjet recording method
US20150258833A1
